Zinc alloy plated steel material having excellent spot weldability and corrosion resistance

By forming a Zn-Mg alloy layer in galvanized alloy steel, controlling the weight ratio and adhesion amount of Mg, the problem of insufficient embrittlement and corrosion resistance of liquid metal during spot welding of galvanized alloy steel is solved, and excellent Spot welding and corrosion resistance meet the needs of high corrosion resistance and environmental protection and economicality.

CN119243156APending Publication Date: 2025-01-03POHANG IRON & STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411284374.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2016-12-26
Filing Date
2017-12-21
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Galvanized alloy steel is prone to liquid metal embrittlement (LME) during spot welding, resulting in brittle cracks. The corrosion resistance of existing galvanized steel is insufficient, especially in deteriorating corrosion environments, which is difficult to meet high demand.

Method used

The Zn-Mg alloy layer is formed by mutual diffusion of Zn and Mg, and the weight ratio of Mg is controlled to be between 0.13 and 0.24, and the adhesion amount of the formed Zn-Mg alloy layer is less than 40 g/m2, and is formed by electromagnetic suspension physical vapor deposition method. The Mg deposited layer is deposited and heat treated to form a Zn-Mg alloy layer, thereby improving the spot weldability and corrosion resistance of galvanized alloy steel.

Benefits of technology

It effectively inhibits the occurrence of embrittlement of liquid metals, significantly improves spot welding properties and corrosion resistance, and ensures excellent environmental protection and economical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243156A_ABST
    Figure CN119243156A_ABST
Patent Text Reader

Abstract

The invention discloses zinc alloy plated steel and a manufacturing method thereof. The zinc alloy plated steel comprises: base material iron; a Zn plating layer formed on the base material iron; and a Zn-Mg alloy layer formed on the Zn plating layer and obtained by interdiffusion of Zn and Mg, the weight ratio of Mg contained in the Zn-Mg alloy layer being 0.13 to 0.24 with respect to the total weight of the Zn plating layer and the Zn-Mg alloy layer, and the sum of the adhesion amounts of the Zn plating layer and the Zn-Mg alloy layer being 40 g / m2 or less (excluding 0 g / m2).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of a Chinese patent application with a filing date of December 21, 2017, a Chinese patent application number of 201780080848.1, and an invention name of “Galvanized alloy steel with excellent spot weldability and corrosion resistance”, and this application claims the priority of a Korean application with application number 10-2016-0178836. Technical Field

[0002] The present invention relates to a galvanized alloy steel material having excellent spot weldability and corrosion resistance, and more particularly to a galvanized alloy steel material having excellent spot weldability and corrosion resistance that can be applied to automobiles, home appliances, building materials, and the like. Background Art

[0003] The galvanizing method, which suppresses the corrosion of iron by cathodic corrosion protection, has excellent anti-corrosion performance and economic efficiency, and is therefore widely used to manufacture steel products with high corrosion resistance. In addition, the demand for galvanized steel products coated with zinc is increasing rapidly in the entire industry, such as automobiles, home appliances, and building materials.

[0004] When this galvanized steel is exposed to a corrosive environment, it has a sacrificial corrosion protection (Sacrificial Corrosion Protection) characteristic in which zinc, which has a lower redox potential than iron, corrodes first, thereby inhibiting the corrosion of the steel. When the zinc in the coating is oxidized, dense corrosion products are formed on the surface of the steel, isolating the steel from the oxidizing atmosphere, thereby improving the corrosion resistance of the steel.

[0005] However, with the advancement of industry, air pollution has increased, the corrosive environment has deteriorated, and strict regulations on resources and energy conservation are being implemented. Therefore, there is an increasing demand for the development of steel with better corrosion resistance than existing galvanized steel. As part of this, various studies are being conducted on the manufacturing technology of galvanized alloy steel that adds elements such as magnesium (Mg) to the coating to improve the corrosion resistance of steel.

[0006] In addition, usually, galvanized steel or zinc alloy steel (hereinafter referred to as "galvanized steel") is processed into parts by processing, etc., and then welded by spot welding, etc. and used as products. In the case of galvanized steel using high-strength steel whose fine structure includes austenite or residual austenite, high P added high-strength interstitial free (IF) steel, etc. as the base material, during spot welding, molten zinc penetrates along the grain boundaries of the base iron, inducing brittle cracks, which is also called liquid metal embrittlement (LME).

[0007] Figure 1This is a photograph showing an enlarged view of a welded portion of a welded component where LME cracks have occurred due to spot welding. Figure 1 In welding, cracks generated above and below the nugget are called Type A cracks, cracks generated at the welding shoulder are called Type B cracks, and cracks generated inside the steel plate due to misalignment of the electrode during welding are called Type C cracks. Among them, Type B cracks and Type C cracks have a great impact on the rigidity of the material, so preventing the occurrence of cracks during welding is a core requirement in this technical field. Summary of the invention

[0008] 1. Technical issues to be resolved

[0009] One of the multiple objects of the present invention is to provide a zinc alloy plated steel material having excellent spot weldability and corrosion resistance.

[0010] (II) Technical solution

[0011] One aspect of the present invention provides a galvanized alloy steel material, comprising: a substrate iron; a Zn coating formed on the substrate iron; and a Zn-Mg alloy layer formed on the Zn coating, obtained by mutual diffusion of Zn and Mg, wherein the weight ratio of Mg contained in the Zn-Mg alloy layer is 0.13 to 0.24 relative to the total weight of the Zn coating and the Zn-Mg alloy layer, and the sum of the adhesion amounts of the Zn coating and the Zn-Mg alloy layer is 40 g / m 2 Below (0g / m 2 except).

[0012] Another aspect of the present invention provides a method for manufacturing a zinc alloy steel material, which comprises the following steps: preparing a Zn-plated steel sheet formed with a Zn coating; suspending a coating material in a vacuum chamber by electromagnetic force and heating it to form a deposition vapor, inducing the deposition vapor to be sprayed toward the Zn-plated steel sheet to form a Mg deposition layer; and heat-treating the Zn-plated steel sheet formed with the Mg deposition layer at a temperature of 250° C. or more and less than 320° C. to form a Zn-Mg alloy layer, wherein the weight ratio of the Mg deposition layer is 0.13 to 0.24 relative to the total weight of the Zn coating and the Mg deposition layer, and the sum of the adhesion amounts of the Zn coating and the Zn-Mg alloy layer is 40 g / m 2 Below (0g / m 2 except).

[0013] (III) Beneficial effects

[0014] As one of the multiple effects of the present invention, the galvanized alloy steel according to the present invention has excellent spot weldability, and thus when high-strength steels whose microstructures include austenite or retained austenite, high-P-added high-strength interstitial free (IF) steels, etc. are used as substrates, the occurrence of liquid metal embrittlement (LME) can also be effectively suppressed.

[0015] Furthermore, the multi-layer zinc alloy-plated steel material according to the present invention can ensure excellent corrosion resistance even with a small amount of coating, and is therefore environmentally friendly and economically excellent.

[0016] The multiple beneficial advantages and effects of the present invention are not limited to the above contents, and can be more easily understood in the process of describing the specific embodiments of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a photograph showing an enlarged view of a welded portion of a welded component where LME cracks have occurred due to spot welding.

[0018] Figure 2 This is the phase equilibrium diagram of Mg-Zn binary alloy.

[0019] Figure 3 This is a schematic diagram showing the corrosion process of plated steel.

[0020] Figure 4 This is a schematic diagram of an electromagnetic levitation physical vapor deposition device.

[0021] Figure 5 This is a photograph of the welded portion observed after spot welding of the zinc alloy-plated steel material of Invention Example 5.

[0022] Best Mode for Carrying Out the Invention

[0023] It is known that in Zn-Mg alloy plated steel, as the Mg content increases, although it is advantageous in terms of corrosion resistance, it is disadvantageous in terms of spot weldability, so the Mg content in the coating is usually controlled to a maximum of about 10% by weight. This is because the Zn-Mg-based intermetallic compounds with low melting points in the Zn-Mg coating are easily dissolved, inducing liquid metal embrittlement. However, according to further research results of the present inventors, it was found that even if the Mg content in the coating exceeds 10% by weight, when the average content is within a certain range and the average grain size of the grains forming the Zn-Mg alloy layer is within a certain range, the spot weldability is significantly improved, thereby completing the present invention.

[0024] Hereinafter, the zinc alloy-plated steel material having excellent spot weldability and corrosion resistance will be described in detail.

[0025] The galvanized alloy steel material of the present invention comprises a base iron and a Zn coating layer and a Zn-Mg alloy layer sequentially formed on the base iron. The shape of the base iron is not particularly limited in the present invention, and can be, for example, a steel plate or a steel wire.

[0026] Furthermore, the alloy composition of the base iron is not particularly limited in the present invention. As an example, the base iron may contain, in weight %, C: 0.10-1.0%, Si: 0.5-3%, Mn: 1.0-25%, Al: 0.01-10%, P: 0.1% or less (except 0%), S: 0.01% or less (except 0%), and the balance Fe and inevitable impurities. In this case, the contents of C, Si, Mn, P and S may satisfy the following relational expression 1. In addition, the fine structure of the base iron having the composition described above may contain austenite or retained austenite.

[0027] [Relationship 1] [C] + [Mn] / 20 + [Si] / 30 + 2 [P] + 4 [S] ≥ 0.3

[0028] (wherein, [C], [Mn], [Si], [P] and [S] represent the contents of the corresponding elements (weight %))

[0029] When the alloy composition and fine structure are as described above, liquid metal embrittlement (LME) becomes a major problem during spot welding. The reason is as follows: That is, the grain boundaries of austenite or retained austenite are weaker than other structures. When stress is applied by spot welding, liquid molten zinc penetrates into the grain boundaries of austenite or retained austenite at the weld to generate cracks, thereby causing liquid metal embrittlement, which is a brittle fracture.

[0030] However, as described below, the present invention minimizes the retention time of the liquid molten zinc, so even if the steel material having the alloy composition and microstructure as described above is used as the base material to produce the galvanized alloy steel material, the occurrence of liquid metal embrittlement can be effectively suppressed. However, of course, the present invention can also be applied when the alloy composition of the base material iron does not meet the above range.

[0031] The Zn plating layer is formed on the base iron to protect the base iron from the influence of the corrosive environment, and can be formed by any method of electroplating, hot-dip plating, and physical vapor deposition (PVD).

[0032] However, when the Zn coating is formed by hot-dip plating, high-resistance Fe2Al5 is inevitably present at the interface between the base iron and the Zn coating, non-conductive Al2O3 is generated on the electrode during welding, and the thickness deviation of the coating is relatively large, which is disadvantageous in terms of spot weldability. Considering these circumstances, the Zn coating is preferably an electroplated layer or a coating formed by physical vapor deposition.

[0033] * The Zn-Mg alloy layer is formed on the Zn plating layer, and is obtained by mutual diffusion of Zn and Mg in the Zn plating layer and the Mg deposition layer as described below.

[0034] The present invention is characterized in that the weight ratio of Mg contained in the Zn-Mg alloy layer is 0.13 to 0.24 relative to the total weight of the Zn plating layer and the Zn-Mg alloy layer, and more preferably the weight ratio of Mg is 0.157 to 0.20.

[0035] The microstructure of the Zn-Mg alloy layer can contain Zn single phase, Mg single phase, Mg2Zn 11 The present inventors have found that when the weight ratio of Mg contained in the Zn-Mg alloy layer is controlled within the range described above relative to the total weight of the Zn plating layer and the Zn-Mg alloy layer, the Zn plating layer and the Zn-Mg alloy layer on the weld portion melt during spot welding and transform into a single-layer alloy layer containing 90% by area or more (including 100% by area) of the MgZn2 alloy phase. In this case, liquid metal embrittlement (LME) is effectively suppressed. Figure 2 It can be seen from the phase equilibrium diagram of the Mg-Zn binary alloy that this is presumably because the melting point of the coating is high, which minimizes the time the molten coating stays in the liquid state. In addition, the present invention does not specifically limit the structure of the remainder of the coating on the welded portion other than the MgZn2 alloy phase. According to an example without limitation, the remainder other than the MgZn2 alloy may be Mg2Zn 11 Alloy phase.

[0036] Among them, the measurement of phase fraction can be carried out by using the standardless Rietveld quantitative analysis method of conventional XRD, and at the same time using a more precise TEM-based crystal orientation mapping technique (TEM-ASTAR) for analysis and measurement, but it is not limited to this. In addition, the phase change process of the Zn-Mg alloy coating can be analyzed by high-temperature in-situ radiation XRD. More specifically, the sample can be heated at a heating rate of 1.3°C / second, 11.3°C / second, and a heating temperature of 780°C. During the thermal cycle of heating and cooling, the XRD spectrum is continuously measured at one frame per second for a total of 900 frames, so as to analyze the phase change process of the Zn-Mg alloy coating, but it is not limited to this.

[0037] According to further research results of the present inventors, the average grain size of the crystal grains constituting the Zn-Mg alloy layer has a significant influence on the corrosion resistance of the plated steel material. Figure 3 This is a schematic diagram showing the corrosion process of plated steel. Figure 3 (a) is a schematic diagram of the case where the grain size is fine. Figure 3 (b) is a schematic diagram of the case where the grain size is coarse. Figure 3 It can be seen that when the grain size is fine, relatively dense and uniform corrosion products are formed when corrosion occurs, which helps to relatively delay corrosion.

[0038] In addition, the average grain size of the grains constituting the Zn-Mg alloy layer also has a considerable influence on the spot weldability of the plated steel. When the average grain size of the grains is below a certain level, the generation of type B cracks is significantly reduced. It is speculated that this is because the active movement of atoms in the molten coating is conducive to ensuring the desired structure.

[0039] As mentioned above, when considering the corrosion resistance and spot weldability of the plated steel, it is necessary to properly control the upper limit of the average particle size of the grains constituting the Zn-Mg alloy layer, and the average particle size of the grains constituting the Zn-Mg alloy layer is preferably controlled to be below 100nm (except 0nm). Wherein, the average particle size refers to the average major diameter of the grains observed and detected in the cross section in the thickness direction of the coating.

[0040] According to one example, the total amount of the Zn plating layer and the Zn-Mg alloy layer can be 40 g / m 2 Below (0g / m 2The greater the sum of the amounts of Zn plating and Zn-Mg alloy layer, the more advantageous it is in terms of corrosion resistance. However, due to the increase in the amount of Zn plating, liquid metal embrittlement (LME) is caused during spot welding. Therefore, considering the weldability, the upper limit of the sum of the amounts of Zn plating and Zn-Mg alloy layer can be limited to the above range. In addition, the preferred range of the sum of the amounts of Zn plating and Zn-Mg alloy layer in terms of corrosion resistance and spot weldability is 10 to 35 g / m 2 The more preferred range is 15 to 30 g / m 2 .

[0041] The galvanized alloy steel material of the present invention described above can be manufactured by various methods, and the manufacturing method is not particularly limited. However, as a specific embodiment, it can be manufactured by the method described below.

[0042] First, the surface of the base iron is pickled, rinsed and dried with a 14 wt % or more HCl aqueous solution to remove foreign matter on the surface, and the natural oxide film is removed by plasma and ion beam, etc., followed by zinc (Zn) plating to prepare a Zn-plated steel material having a Zn plating layer. As described above, the Zn plating layer on the base iron can be formed by electroplating or physical vapor deposition.

[0043] Then, a Mg deposition layer is formed on the Zn plating layer. At this time, the Mg deposition layer is preferably formed by an electromagnetic levitation physical vapor deposition method with an electromagnetic stirring effect.

[0044] Among them, the electromagnetic suspension physical vapor deposition method is a method that utilizes the following phenomenon: when a high-frequency power supply is applied to a pair of electromagnetic coils that generate an AC electromagnetic field to generate electromagnetic force, the coating material (Mg in the present invention) is suspended in the air in a space surrounded by the AC electromagnetic field without external assistance, and the suspended coating material generates a large amount of deposition vapor (metal vapor). Figure 4 A schematic diagram of a device for electromagnetic levitation physical vapor deposition is shown. Figure 4 As shown, a large amount of deposition vapor formed by the method described above is sprayed at high speed onto the surface of the material to be coated through a plurality of nozzles of a vapor distribution box to form a deposition layer.

[0045] In a conventional vacuum deposition apparatus, a coating material is provided inside a crucible, and the coating material is easily vaporized by heating the crucible provided with the coating material. In this case, it is difficult to supply sufficient heat energy to the coating material due to melting of the crucible, heat loss caused by the crucible, etc. Therefore, not only the deposition speed is slow, but also there is a certain limit on the miniaturization of the grain size constituting the deposited layer.

[0046] However, unlike conventional vacuum deposition, electromagnetic levitation physical vapor deposition has no temperature constraints and can expose the coating material to higher temperatures, thereby enabling not only high-speed deposition but also miniaturization of the grain size of the final deposited layer.

[0047] During the deposition process, the vacuum degree inside the vacuum deposition chamber is preferably adjusted to 1.0×10 -3 mbar to 1.0×10 -5 mbar conditions, in this case, can effectively prevent the formation of oxides during the deposition process caused by the increase in brittleness and the reduction of physical properties.

[0048] In the deposition process, the temperature of the suspended coating material is preferably adjusted to 700°C or more, more preferably to 800°C or more, and even more preferably to 1000°C or more. When the temperature of the suspended coating material is lower than 700°C, the grain refinement effect may not be fully ensured. In addition, the higher the temperature of the suspended coating material, the more conducive it is to achieve the desired technical effect. The upper limit is not particularly limited in the present invention, but when the temperature is above a certain level, not only the effect is saturated, but also the process cost is too high. Taking these circumstances into account, the upper limit of the temperature can be limited to 1500°C.

[0049] The temperature of the Zn-plated steel before and after deposition is preferably adjusted to below 100°C. When the temperature of the Zn-plated steel exceeds 100°C, the bending in the width direction caused by the temperature unevenness of the steel plate in the width direction will hinder the maintenance of vacuum when passing through the multi-stage graded decompression system on the outlet side.

[0050] Then, the Zn-plated material with the Mg deposit layer formed thereon is heat-treated at a temperature of 250°C or higher to form a Zn-Mg alloy layer. The reason for limiting the heat treatment temperature to 250°C or higher is that when the heat treatment temperature is lower than 250°C, mutual diffusion of Zn and Mg in the Zn plating layer and the Mg deposit layer is not easy to occur. In addition, the upper limit of the heat treatment temperature is not particularly limited in the present invention, but when the heat treatment temperature is higher than 320°C, a brittle alloy phase of zinc and iron is formed at the interface between the substrate iron and the Zn plating layer, which is disadvantageous in terms of sealant adhesion. In view of these circumstances, the upper limit of the heat treatment temperature can be limited to a temperature lower than 320°C.

[0051] The heat treatment method is not particularly limited in the present invention, but can be performed by induction heating or ultraviolet heating, for example, and the heating time can be 3 seconds to 100 seconds. When the heating time is less than 3 seconds, alloying is insufficient and a part of the Mg deposit layer remains. On the other hand, when the heating time exceeds 100 seconds, alloying between the steel sheet and the Zn plating layer may occur. DETAILED DESCRIPTION

[0052] The following is a more detailed description of the embodiments of the present invention. However, the description of these embodiments is only used to illustrate the implementation mode of the present invention, and the present invention is not limited to the contents described in the embodiments. This is because the scope of the present invention is determined by the matters described in the claims and the matters reasonably derived therefrom.

[0053] (Example)

[0054] An electrogalvanized steel sheet having an electrogalvanized layer having a thickness as shown in Table 1 below is formed on a high-strength cold-rolled steel sheet for automobiles having a thickness of 1.4 mm, wherein the cold-rolled steel sheet contains, by weight%, 0.16% C, 1.43% Si, 2.56% Mn, 0.04% Al, 0.006% P, 0.0029% S, and the balance Fe and inevitable impurities, and is prepared by using Figure 4 The device (vacuum degree is 3.2×10 -3 mbar) to form a Mg deposit layer having a thickness as shown in the following Table 1. In all examples, when forming the Mg deposit layer, the conditions are constant: the current applied to a pair of electromagnetic coils is 1.2 kA, the frequency applied to the pair of electromagnetic coils is 60 kHz based on 2 kg of the deposited material, the temperature of the suspended coating material is 1000°C, and the temperature of the steam distribution box is 900°C. In addition, the temperature of the substrate iron before and after deposition is maintained at 60°C. The electro-galvanized steel sheet with the Mg deposit layer formed thereon passes through the exit strip lock (Exit Strip-lock) into the atmosphere, and is subjected to alloying heat treatment in a heat treatment zone (Zone) using induction heating. In all examples, the heat treatment temperature is constant at 280°C, and the heat treatment time is constant at 10 seconds.

[0055] Then, the total adhesion amount and Mg weight ratio of the galvanized alloy steel produced by the inductively coupled plasma (ICP) method were measured. More specifically, the test piece was cut into 80mm×80mm size, and after the surface was degreased, the first evaluation (W1: 0.0000g) was performed using a high-precision scale. After that, a special column with a diameter of 54.5mm (dia) of the O-Ring was attached to the front part using a clamp, and it was tightly combined to prevent leakage of the solution. After that, 30cc of 1:3HCl solution was added, and 2 to 3 drops of inhibitor were added. After the process of generating H2 gas on the surface was completed, the solution was collected in a 100cc volumetric bottle. At this time, all the remaining amount on the surface was collected using a washing bottle, and less than 100cc was collected. After that, after the test piece was completely dried, the second evaluation (W2) was performed, and the difference between the first evaluation value and the second evaluation value was divided by the value per unit area as the total adhesion amount of the galvanized alloy steel. In addition, the collected solution was used as an object, and the Mg content was measured by the ICP method, and the result was used as the weight ratio of Mg.

[0056] Then, the average grain size of the crystal grains constituting the Zn-Mg alloy layer was measured. As a result of the measurement, the average grain size of the crystal grains constituting the Zn-Mg alloy layer in all the examples was 100 nm or less.

[0057] Then, the weldability and corrosion resistance of the produced zinc alloy plated steel materials were evaluated, and the results are shown in Table 1 below.

[0058] More specifically, regarding weldability, according to SEP 1220-2, test pieces of 40 mm×120 mm were cut, and each test piece was spot welded 100 times in total. The presence and size of type B cracks were measured and evaluated according to the following criteria.

[0059] 1. Excellent: No Type B cracks were found in any of the test pieces.

[0060] 2. Excellent: Type B cracks occur in some or all of the test pieces, and the average length of the Type B cracks is less than 0.1 times the thickness of the base steel (cold-rolled steel sheet)

[0061] 3. Normal: Type B cracks occur in part or all of the test pieces, and the average length of the Type B cracks is less than 0.2 times the thickness of the base steel (cold-rolled steel sheet)

[0062] 4. Bad: Type B cracks occur in part or all of the test pieces, and the average length of the Type B cracks exceeds 0.2 times the thickness of the base steel (cold-rolled steel sheet)

[0063] Regarding corrosion resistance, each multilayer zinc alloy-plated steel material was cut into a test piece of 75 mm×150 mm in size, and then subjected to a salt spray test according to JIS Z2371. The time until initial red rust was generated was measured and evaluated according to the following criteria.

[0064] 1. Excellent: single-sided adhesion is 60g / m 2 Compared with galvanized steel sheets (GI steel sheets), the time for red rust to form is more than twice as long

[0065] 2. Normal: 60g / m2 on one side 2 When the time for red rust to form is equal to or less than twice that of galvanized steel sheets (GI steel sheets)

[0066] 3. Bad: The adhesion amount on one side is 60g / m 2 Compared with galvanized steel sheets (GI steel sheets), the time for red rust to form is shorter

[0067] [Table 1]

[0068]

[0069]

[0070] Referring to Table 1, it can be confirmed that in Invention Examples 1 to 13 that satisfy all the conditions proposed in the present invention, not only the corrosion resistance is excellent, but also the spot weldability is very excellent. In addition, it can be confirmed that in order to ensure more excellent spot weldability, preferably, the weight ratio of Mg is 0.157 to 0.20, and the total amount of the Zn plating layer and the Zn-Mg alloy layer is controlled to 35 g / m 2 the following.

[0071] On the other hand, in Comparative Examples 1 to 6, it was confirmed that the weight ratio of Mg was out of the range proposed in the present invention, and thus the spot weldability was poor.

[0072] in addition, Figure 5 This is a photograph of the welded portion observed after spot welding of the zinc alloy-plated steel material of Invention Example 5. Figure 5 It can be visually confirmed that the welded portion of the galvanized alloy steel material of the present invention not only has no type B cracks, but also has no type C cracks at all.

[0073] The embodiments of the present invention have been described in detail above, but the scope of rights of the present invention is not limited thereto, and it is obvious to those skilled in the art that various modifications and variations can be made without departing from the technical concept of the present invention described in the claims.

Claims

1. A galvanized alloy steel material, comprising: Base material iron; A Zn plating layer formed on the base iron; and a Zn-Mg alloy layer formed on the Zn plating layer and obtained by mutual diffusion of Zn and Mg, The weight ratio of Mg contained in the Zn-Mg alloy layer is 0.13 to 0.230 relative to the total weight of the Zn plating layer and the Zn-Mg alloy layer. The total amount of the Zn coating and the Zn-Mg alloy layer is 40 g / m 2 Below and 0g / m 2 except, The average grain size of the crystal grains constituting the Zn-Mg alloy layer is 100 nm or less, excluding 0 nm.

2. The galvanized alloy steel material according to claim 1, wherein: The weight ratio of Mg contained in the Zn-Mg alloy layer is 0.157 to 0.20 relative to the total weight of the Zn plating layer and the Zn-Mg alloy layer.

3. The galvanized alloy steel material according to claim 1, wherein: The total amount of the Zn coating and the Zn-Mg alloy layer is 10 to 35 g / m 2 .

4. The galvanized alloy steel material according to claim 1, wherein: When the galvanized alloy steel is spot welded, the Zn coating and Zn-Mg alloy layer on the weld portion are transformed into a single alloy layer, and the single alloy layer on the weld portion contains more than 90 area % and 100 area % of the MgZn2 alloy phase.

5. The galvanized alloy steel material according to claim 1, wherein: When spot welding is performed according to SEP 1220-2, the average length of type B cracks is 0.1 times or less the thickness of the base iron.

6. The galvanized alloy steel material according to claim 1, wherein: The Zn coating is a Zn electroplating layer or a Zn coating formed by physical vapor deposition.

7. The galvanized alloy steel material according to claim 1, wherein: In terms of weight %, the base iron comprises: C: 0.10-1.0%, Si: 0.5-3%, Mn: 1.0-25%, Al: 0.01-10%, P: 0.1% or less and excluding 0%, S: 0.01% or less and excluding 0%, and the balance Fe and unavoidable impurities.

8. The galvanized alloy steel material according to claim 7, wherein: The contents of C, Si, Mn, P and S contained in the base material iron satisfy the following relational formula 1: [Relationship 1] [C] + [Mn] / 20 + [Si] / 30 + 2 [P] + 4 [S] ≥ 0.3 Herein, [C], [Mn], [Si], [P] and [S] represent the contents of the corresponding elements, and the unit is weight %.

9. The galvanized alloy steel material according to claim 7, wherein: The microstructure of the base iron includes one or more of austenite and retained austenite.

10. A method for manufacturing a galvanized alloy steel material, comprising the following steps: preparing a Zn-plated steel sheet having a Zn plating layer formed thereon; suspending a coating substance by electromagnetic force in a vacuum chamber and heating it to form a deposition vapor, and inducing the deposition vapor to spray toward the surface of the Zn-plated steel sheet to form a Mg deposition layer; and The Zn-plated steel sheet having the Mg deposit layer formed thereon is subjected to heat treatment at a temperature of 250° C. or higher and lower than 320° C. to form a Zn-Mg alloy layer. Relative to the total weight of the Zn plating layer and the Mg deposition layer, the weight ratio of the Mg deposition layer is 0.13 to 0.230, The total amount of the Zn coating and the Zn-Mg alloy layer is 40 g / m 2 Below and 0g / m 2 except, The temperature of the suspended coating material is above 1000°C, The temperature of the Zn-plated steel sheet before and after deposition is 100°C or less. The heat treatment is performed by induction heating or ultraviolet heating for 3 seconds to 100 seconds.

11. The method for manufacturing a zinc alloy-plated steel material according to claim 10, wherein: The weight ratio of the Mg deposition layer is 0.157 to 0.20 relative to the total weight of the Zn plating layer and the Mg deposition layer.

12. The method for manufacturing a zinc alloy-plated steel material according to claim 10, wherein: The Zn coating is formed by electroplating or physical vapor deposition.

13. The method for manufacturing a zinc alloy-plated steel material according to claim 10, wherein: The vacuum degree inside the vacuum chamber is 1.0×10 -3 mbar to 1.0×10 -5 mbar.